Search for the decay B0s → D*∓π± - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
A search for the decay B0s→D*∓π± is presented using a data sample corresponding to an integrated luminosity of 1.0 fb−1 of pp collisions collected by LHCb. This decay is expected to be mediated by a W-exchange diagram, with little contribution from rescattering processes, and therefore a measurement of the branching fraction will help us to understand the mechanism behind related decays such as B0s→π+π− and B0s→DD̄. Systematic uncertainties are minimized by using B0→D*∓π± as a normalization channel. We find no evidence for a signal, and set an upper limit on the branching fraction of B(B0s→D*∓π±)<6.1(7.8)×10−6 at 90% (95%) confidence level.
Im Titel sind "0", "∓" und "±" hochgestellt und "s" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 585
Gesehen am 20.04.2021